Purity of Faith, Madhhab Partisanship, and Legitimising Ideology in the Great Seljuq Sultanate - Tor, Deborah G. (Islamic law and society, 2025)
The madhhab is usually investigated from the standpoint of fiqh. But there was also a social aspect to the importance of the madhhab, which at no time played a more crucial social role than during the Seljuq period (1040–1194). In particular, Ḥanafī madhhab affiliation became both the post-conquest ideological justification for Seljuq rule, and the glue holding together the two elements of the Seljuq ruling class: The Turkish magnates and the Khurasani bureaucrats. This article proves three points: First, that the original Seljuq conquest neither looked like nor purported to be the religious mission the Seljuqs later claimed it was; second, it traces the post-facto madhhab-based justification of their rule which the Seljuqs adopted, and its success in obtaining Khurasani support for the Seljuq regime; and, finally, it shows also the negative consequences this ideology of partisan Ḥanafism had on the internal peace of their realm and its urban flourishing.